2007
DOI: 10.1007/s11145-007-9065-y
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated strategy development instruction for writing an opinion essay: Effects for six students with emotional/behavior disorders

Abstract: A multiple-probe across-subjects design was used to examine persuasive writing performance of six 2 nd -through 5th-grade students with emotional/behavior disorders (EBD). Students' writing was evaluated before and after self-regulated strategy development (SRSD) instruction for the POW (Pick my idea, Organize my notes, Write and say more) + TREE (Topic sentence, Reasons -three or more, Ending, Examine) strategy. Students' essays written during and immediately after instruction indicated that the students had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 20 publications
6
70
0
3
Order By: Relevance
“… a writing process model in which students are encouraged to plan, draft, edit and revise their writing (Englert et al 1991;De La Paz and Graham 2002;Troia and Graham 2002)  self-motivation (in the form of personal target-setting -one aspect of self-regulated strategy development) (Graham et al 2005)  some degree of cognitive reasoning training in addition to the natural cognitive development that takes place with maturation (Englert et al 1991;Ferretti et al 2000), for example the selfregulated strategy development suggested by Mason and Shriner (2008)  peer collaboration, thus modelling a dialogue that (it is hoped) will become internal and constitute "thought" (Englert et al 1991)  explicit and very clear explanations for students of the processes to be learned, though there is a suggestion in Reznitskaya et al (2008) that these are less important than peer discussion.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… a writing process model in which students are encouraged to plan, draft, edit and revise their writing (Englert et al 1991;De La Paz and Graham 2002;Troia and Graham 2002)  self-motivation (in the form of personal target-setting -one aspect of self-regulated strategy development) (Graham et al 2005)  some degree of cognitive reasoning training in addition to the natural cognitive development that takes place with maturation (Englert et al 1991;Ferretti et al 2000), for example the selfregulated strategy development suggested by Mason and Shriner (2008)  peer collaboration, thus modelling a dialogue that (it is hoped) will become internal and constitute "thought" (Englert et al 1991)  explicit and very clear explanations for students of the processes to be learned, though there is a suggestion in Reznitskaya et al (2008) that these are less important than peer discussion.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Therefore the findings that we report here should be read with these caveats in mind. The foci of these three studies are: social and cognitive processes underlying the development of argumentational knowledge (Reznitskaya et al 2007); the effects of content and audience awareness goals for revision of persuasive essays (Midgette et al 2008); and self-regulated strategy development instruction for writing an opinion essay (Mason and Shriner 2008).…”
Section: Recent Research Literaturementioning
confidence: 99%
“…Raters were given anchor papers representing each score level. The use of holistic scoring, with anchor points, was developed and validated in previous research (Graham et al, 2005;Harris et al, 2006;Mason & Shriner, 2007). The anchor papers used for scoring in this study were developed and used in the prior SRSD for quick writing studies (Author).…”
Section: Organizational Qualitymentioning
confidence: 99%
“…This is not an uncommon finding. Previous SRSD studies have reported decreases in performance at maintenance (Mason & Shriner, 2008;Mastropieri et al, 2009Mastropieri et al, , 2010. It is uncertain why the mean number of words written at maintenance for the comparison group increased when compared to their mean performance at pre-and posttest.…”
Section: Discussionmentioning
confidence: 92%
“…How do the characters feel?) (Adkins, 2005;Lane et al, 2008;Lane et al, 2010) or persuasive writing using POWCTREE Mason & Shriner, 2008).…”
mentioning
confidence: 99%